2021
DOI: 10.3389/fendo.2021.662543
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Thyroid Volume and Physical Growth in Pubertal Girls: Thyroid Volume Indexes Need to Be Applied to Thyroid Volume Assessments

Abstract: BackgroundThyroid volume (Tvol) is associated with many factors, but the current reference values for Tvol in children with sufficient iodine intake are inappropriate and need to be updated. Moderate changes in thyroid morphology and accentuated increases in body fat percentage occur during puberty as an adaption of the body and sexual development occurs. This study aimed to evaluate the influences of physical growth on Tvol and propose an easily applicable method for conducting Tvol assessments in pubertal gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Pre-schoolers (3–6 years) had a median UIC of 181 μg/L for those living in rural areas and 182 μg/L for those living in urban areas; school-aged children (7–12 years) had a median of 191 μg/L for those living in rural areas and 166 μg/L for those living in urban areas; and adolescents (13–18 years old) had a median of 193 μg/L for those living in rural areas and 186 μg/L for those living in urban areas [ 86 ]. Similarly, in another study, children aged 8 years had UIC of 158 μg/l in rural areas and 161 μg/L in urban areas; children aged 9 years had 180 μg/L in rural areas and 157 μg/L in urban areas; and children aged 10 years had 185.4 μg/L in rural areas and 180 μg/L in urban areas [ 101 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Pre-schoolers (3–6 years) had a median UIC of 181 μg/L for those living in rural areas and 182 μg/L for those living in urban areas; school-aged children (7–12 years) had a median of 191 μg/L for those living in rural areas and 166 μg/L for those living in urban areas; and adolescents (13–18 years old) had a median of 193 μg/L for those living in rural areas and 186 μg/L for those living in urban areas [ 86 ]. Similarly, in another study, children aged 8 years had UIC of 158 μg/l in rural areas and 161 μg/L in urban areas; children aged 9 years had 180 μg/L in rural areas and 157 μg/L in urban areas; and children aged 10 years had 185.4 μg/L in rural areas and 180 μg/L in urban areas [ 101 ].…”
Section: Resultsmentioning
confidence: 93%
“…In Hebei, the median UIC was 419 μg/L; additionally, 68% of the study populations were > 300 μg/L, while this was 28% at the national level [ 46 , 100 ]. Two studies in Zhejiang province showed higher UIC in rural populations versus urban; however, this was not significant [ 86 , 101 ]. Pre-schoolers (3–6 years) had a median UIC of 181 μg/L for those living in rural areas and 182 μg/L for those living in urban areas; school-aged children (7–12 years) had a median of 191 μg/L for those living in rural areas and 166 μg/L for those living in urban areas; and adolescents (13–18 years old) had a median of 193 μg/L for those living in rural areas and 186 μg/L for those living in urban areas [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it is widely acknowledged that TSH plays a significant role in promoting nodule development and hastening nodule growth in adults (36), the relationship between TSH and TNs in euthyroid individuals remains inconclusive. One previous study reported TSH was not correlated with thyroid nodule formation (37), however other studies found that lower TSH levels were associated with a higher prevalence of TNs both in adolescents (13) and adults (15), which is consistent with the results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in our country, the most important predictors of TV were stated as body weight, body surface area and height, respectively (5). Differences of countries or regions of a country, non homogeneous age range distribution in the sample group, differences of pubertal assessments at certain ages, were not taken into account while determining TV reference cards (6,7). So, diagnostic problems may occur when using these reference cards; such as sometimes detecting goiter in individuals without having goiter, or performing normal evaluations in individuals with goiter.…”
Section: Introductionmentioning
confidence: 99%